Optimization of the healthy village program to improve community healthy living behaviors - Tia Nur Annisa (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: The Healthy Village Program is a community-based health promotion initiative designed to strengthen clean and healthy living behaviors in rural communities through participatory empowerment strategies. Persistent challenges related to environmental sanitation, household waste management, and limited public engagement in healthy practices indicate the need for sustainable educational and preventive interventions. Objective: This community service project aimed to optimize the Healthy Village Program through health education and community empowerment to improve healthy living behaviors among rural residents. Methods: A promotive–preventive, community empowerment-based approach was employed. The intervention included health education sessions, training on healthy environmental management, demonstrations of clean and healthy living practices, and community mentoring. The program involved 80 village residents as participants. Evaluation was conducted using process, output, and outcome indicators, including participant characteristics and changes in healthy living behaviors before and after the intervention. The assessed behaviors comprised household waste management, handwashing with soap, use of proper sanitation, participation in environmental cleanliness activities, and implementation of healthy family practices. Results: Most participants were aged 36–55 years (47.5%), female (57.5%), had a secondary education level (42.5%), and were farmers or fishers (35.0%). Before the intervention, community participation in environmental activities was generally low, with 60.0% categorized as inactive. Following the intervention, marked improvements were observed across all behavioral indicators. Good household waste management increased from 35.0% to 70.0%, handwashing with soap from 45.0% to 85.0%, use of proper sanitation from 50.0% to 80.0%, participation in environmental cleanliness activities from 32.5% to 72.5%, and implementation of healthy family practices from 37.5% to 77.5%. Conclusion: Optimizing the Healthy Village Program through integrated health education and community empowerment was associated with improved healthy living behaviors in the rural community. Sustained implementation, regular behavioral monitoring, and multisectoral collaboration are recommended to strengthen long-term program sustainability.